Leaving It All Behind to Travel: Venturing Uncertainty as a Means to Personal Growth and Authenticity. (July 2013) - Hirschorn, Sara; Hefferon, Kate
The potential for personal growth in cross-cultural travel has been posited by numerous psychologists; however, a "gaping hole" in empirical research has left these hypotheses unexplored. Meanwhile, rapidly increasing numbers of people are choosing to leave their careers to pursue a personal dream of extensive foreign travel. The aim of this study was to explore the motivations, psychological experiences, and outcomes from travel in this growing "career-break" demographic. Ten men and women who had exited their careers to pursue extensive culturally engaging travel participated in an individual semistructured interview that was analyzed using constructivist grounded theory. Three main themes emerged: an existential yearning to travel, "jumping off the ledge" (courage), and discovering authenticity. Personal growth occurred via adversity within the travel experience itself, but also at the pretravel stage of departure, where leaving security and venturing uncertainty was experienced with "milestone" significance and, for some, as a seismic event akin to trauma. Future research should explore the potential for a new type of intrinsically emerging trauma in posttraumatic growth and the potential for anxiety as a positive construct in authentic becoming and growth.